The Effect Of Training Using Teaching Model On Learning Some Basic Skills In Handball - Hamza, Israa (Journal of Physical Education, 2011)
Sports play an important role in al fields of educational life. Thus, sports has witnessed a great advance in methods of teaching it, the different styles that suit modern students and facilitate the process of learning. The problem of the research lays in using different teaching styles in physical education to help students reach the best level of learning. The researcher proposed designing exercises and a model to identify their effects on learning the basic skills of handball. The aims of the research: 1. Identifying the effect of using exercises with a teaching model on learning the basic skills of handball. 2. Identifying the differences in the proposed exercises' posttests on learning some skills of handball. The Hypotheses of the research: 1. There are significant statistical differences between the two groups using exercises and teaching model on learning some basic skills in handball. 2. There are significant statistical differences in posttests' results in the exercises used for learning some basic skills in handball. The Procedures: The researcher used the experimental method. The subjects were (12) fourth year students of Teacher preparation Institute, Baghdad of the academic year 2009 - 2010. The researcher conducted a pilot study to clarify the skill tests that were applied on the subjects. She also used standardized tests to achieve the aims of the research. After collecting the data, the results were treated using proper statistical methods. The results showed the development of the experimental group that used the teaching model to learning the basic skill of handball. Conclusions and Recommendations: The researcher came up with the following conclusions: 1. The designed exercises have a positive effect on learning the basic skills of handball. 2. The method of using teaching model has the greatest positive effect on learning the basic skills in handball . Finally the researcher recommended the following: 1. Using the teaching sessions along with the exercises to teach some basic skills in handball. 2. The necessity of using the teaching model in learning the basic skills of handball